The "Wage-Productivity" Theory of Underemployment: A Refinement - Yotopoulos, Pan A. (Review of Economic Studies, 1965)
Journal Article The “Wage-Productivity” Theory of Underemployment: A Refinement Get access Pan A Yotopoulos Pan A Yotopoulos University of Wisconsin, Milwaukee Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 32, Issue 1, January 1965, Pages 59–66, https://doi.org/10.2307/2296332 Published: 01 January 1965